2012
DOI: 10.1002/cyto.a.22083
|View full text |Cite
|
Sign up to set email alerts
|

Automatic neutrophil nucleus lobe counting based on graph representation of region skeleton

Abstract: Abnormal neutrophil nucleus lobation (like left shift and right shift) helps to diagnose for some clinical conditions. Currently, quantification of it depends on the manual microscopic inspection of blood smears by clinicians. The quality of the manual inspection is extremely limited by the efficiency of clinicians and their medical background. This article proposed an automatic lobe counting method based on the graph representation of the nucleus region skeletons. Skeletons of the segmented nucleus regions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Generally, the analysis is made by biomedical technologists under the microscope by counting the number of nuclear segments according to the rule of threads and the rule of thirds. Thus, the new methods for fully automatic registration of neutrophi ls nuclear shape (18)(19)(20)(21) should combine both lobe counting according to the rule of thirds and calculation of the circularity index based on the automatically reconstructed boundaries of the lobes (nuclear perimeter) and their area. Interestingly, almost all reports of pseudo PHA (hyposegmentation) were described before the mid 1980's.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the analysis is made by biomedical technologists under the microscope by counting the number of nuclear segments according to the rule of threads and the rule of thirds. Thus, the new methods for fully automatic registration of neutrophi ls nuclear shape (18)(19)(20)(21) should combine both lobe counting according to the rule of thirds and calculation of the circularity index based on the automatically reconstructed boundaries of the lobes (nuclear perimeter) and their area. Interestingly, almost all reports of pseudo PHA (hyposegmentation) were described before the mid 1980's.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it cannot be excluded that heterochromatinization is more extensive in hyperlobulated nuclei, leading to a smaller nuclear area and consequently to a lower circularity index (1,17). Thus, the new methods for fully automatic registration of neutrophi ls nuclear shape (18)(19)(20)(21) should combine both lobe counting according to the rule of thirds and calculation of the circularity index based on the automatically reconstructed boundaries of the lobes (nuclear perimeter) and their area. In the first case, it is the link to the clinically well-established nuclear classification of neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting study into the classification of white blood cells (WBCs) is reported in [14]. In some studies, only segmentation aspects are discussed [15,16], while a neural network-based classifier of cytotypes in the hematological smear of a healthy subject was described in [17]: starting from digital scans of hematological preparations, it showed over 95% accuracy. Many other papers report interesting results about this last theme [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…How to compare the skeleton similarity between the query sketch and 2D views of 3D model is crucial. There are three types of algorithms to compare the skeleton similarity, respectively tree matching algorithm [13], path similarity algorithm [14] and graph representation algorithm [15]. Dragan F F et al [16] found that the tree descriptor represents the topological features of the skeleton, but the maximal isomorphic subtrees are obtained by searching for the longest matching substrings which would lead to higher time complexity.…”
Section: Introductionmentioning
confidence: 99%